A low-voltage ride-through strategy using mixed potential function for three-phase grid-connected PV systems - Meghdad Fazeli (Electric Power Systems Research, 2019)
This paper presents a new control strategy for low-voltage ride-through for 3-phase grid-connected photovoltaic systems. The proposed fault ride through control algorithm, which is designed based on mixed potential function, can protect the inverter from overcurrent failure under both symmetric and asymmetric faults, reduce the double frequency oscillation and provides reactive power support by applying a voltage compensation unit. With the proposed method, the inverter can also inject sinusoidal current during asymmetric faults. The method does not require a hard switch to switch from the Maximum Power Point Tracking (MPPT) to a non-MPPT algorithm, which ensures a smooth transition.